An Anglican Odyssey: The Ecumenical Vision of Canon David John Garland (1864–1939) OBE and his Hidden Christian Agenda for Anzac Day - Moses, John Anthony (Journal of Anglican studies, 2023)
There is still much unclear about the nature of the origins of Australia's most respected and hallowed national day, namely Anzac Day, 25 April, and about who was primarily responsible for instituting a day of solemn commemoration for the fallen in the Great War of 1914-18. Much has been written by mostly unqualified would-be "authorities" that is either patently false, uninformed or hostile to the commemoration. This is either because of resentment in some quarters of the distinctly Anglican contribution to the nature of the commemoration or pacifist misunderstanding that the celebration of Anzac Day is somehow a glorification of war. This paper based on original research into the files of the Queensland Anzac Day Commemoration Committee establishes the key role of Canon David John Garland (1864-1939) in shaping a liturgy of civic religion for the day which he hoped would become a means of reminding the population of their calling as part of the British Empire to emphasize the reign of Almighty God over all nations of the earth. That was the hidden Christian agenda in the mind of Canon Garland. Naturally he had his opponents to this objective.